GREEN MUSTARD PRODUCTION WITH COMBINATION OF TRICHODERMA AND NPK ON ULTISOL SOIL - Amelia, Avivah; Nofrianil; Syahardi, Amri (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Development of green cabbage production on suboptimal land, one of which is ultisol soil. Efforts to increase production with inorganic fertilizer, namely NPK, have a negative impact on agricultural land or reduce soil fertility quality through continuous use. Efforts to reduce the use of inorganic fertilizer, one of the technologies is the use of biofertilizer microorganisms. Trichoderma sp as a biological fertilizer, its role as a biological control agent against pathogens, has a positive impact on the plant root system, growth and development and plant production. The aim of the research is to analyze the response of green cabbage plants to the application of NPK fertilizer and Trichoderma sp. Carrying out research on the Payakumbuh State Agricultural Polytechnic Campus, from February to April 2025. Field experimental research method with Randomized Block Design. Treatments consist of 100% application of inorganic NPK fertilizer, (P1); Trichoderma sp 10ml/liter water + 50% NPK fertilizer, (P2); Trichoderma sp 13 ml/liter water + 50% NPK fertilizer, (P3); Trichoderma sp 15 ml/liter water + 50% NPK fertilizer. Each treatment is grouped into six groups, resulting in a total of 24 experimental units. The application of 10 ml Trichoderma sp + 50% NPK is capable of enhancing plant growth and fresh weight production to a value similar to that obtained with the application of 100% NPK. Increasing the dose of Trichoderma sp applied can enhance the development of the plant's root system. The application of Trichoderma sp can reduce the use of inorganic fertilizer by 50%.